The elements of the drama in training techniques of cognitive behavioral therapy - Prochazka, Roman; Ruzicka, Michal (e-Pedagogium, 2010)
The authors have defined the intersections of dramatherapy and cognitive behavioral therapy. There is a hypothesis, that both of the approaches can use their useful methods for more effectiveness of the therapy. There were defined two new terms: the behavioral drama and the cognitive drama. The authors will work on this topic onwards and in the future they will present the results on others conferences, workshops and in the scientific articles.
Keywords: Cognitive behavioral therapy; case report; drama; drama therapy; phobia; anxiety